2017
DOI: 10.12944/cwe.12.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Visitors Experiences in Different Zoo Exhibits

Abstract: Zoos help people to learn through exhibiting the relationships of animals in nature. Therefore, they have the important missions of education and protection of wild life. Most of these missions are achieved through visitors' experiences in exhibit areas. Therefore, it is important to understand visitors' experiences in the zoo and know the reasons that affect these experiences. Animals should exhibit normal behaviors actively to enable visitors to have positive experiences during their visits. For this reason,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…We also found that the more positive visitor attitudes were toward penguins, their welfare, the enclosure, experience with the penguins and learning, the higher visitor ratings were for penguin welfare, the enclosure and visitor experience. Our results aligns with previous research that also indicates zoo visitors have positive attitudes toward zoo animals and their enclosures when zoos provide positive experiences for visitors (Woods, 2002 ; Clayton et al, 2009 ; Miller et al, 2013 ; Yilmaz et al, 2017 ). Consequently, the present study results are encouraging for both zoos as it suggests the two zoos are providing positive experiences for visitors at the penguin exhibit that may be related to positive visitor attitudes which is important for the overall ethical foundation of zoos (Maple and Perdue, 2013 ; Sherwen et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…We also found that the more positive visitor attitudes were toward penguins, their welfare, the enclosure, experience with the penguins and learning, the higher visitor ratings were for penguin welfare, the enclosure and visitor experience. Our results aligns with previous research that also indicates zoo visitors have positive attitudes toward zoo animals and their enclosures when zoos provide positive experiences for visitors (Woods, 2002 ; Clayton et al, 2009 ; Miller et al, 2013 ; Yilmaz et al, 2017 ). Consequently, the present study results are encouraging for both zoos as it suggests the two zoos are providing positive experiences for visitors at the penguin exhibit that may be related to positive visitor attitudes which is important for the overall ethical foundation of zoos (Maple and Perdue, 2013 ; Sherwen et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is notable, therefore, that we also found evidence to support a positive effect of biodiversity on interest within our smaller public exhibit study. This showed that phyletic richness effects on interest were maintained in a setting that allowed animal movement and behaviour, which can alter human interest in organisms 52 , 53 (Fig. 2a ).…”
Section: Discussionmentioning
confidence: 94%
“…Image-based, online surveys provide experimental control and large sample sizes but miss animal movement and behaviour which can enhance human engagement with natural scenes 52 , 53 . It is notable, therefore, that we also found evidence to support a positive effect of biodiversity on interest within our smaller public exhibit study.…”
Section: Discussionmentioning
confidence: 99%
“…Smart et al (2021) found similar results, interpretation located in an immersive exhibit having not only increased attraction power, but increased holding power also. Additionally, previous studies show that immersive exhibits on the whole are more attractive for zoo visitors (A. Moss et al, 2008; Ross & Gillespie, 2009; Yılmaz et al, 2017). This appears to carry over to interpretation too, suggesting visitors are more inclined to seek out information about a species if they feel more immersed in that species' environment.…”
Section: Discussionmentioning
confidence: 95%